Association between lower estimated premorbid intelligence quotient and smoking behavior in patients with schizophrenia - Hidese, Shinsuke (Schizophr Res Cogn, 2018)
AIM: We aimed to investigate the involvement of premorbid intelligence quotient in higher prevalence of smoking in patients with schizophrenia. METHODS: Participants included 190 patients with schizophrenia (mean ± standard deviation age: 37.7 ± 10.8 years; 88 males and 102 females) and 312 healthy individuals (mean ± standard deviation age: 38.1 ± 13.8; 166 males and 146 females), matched for age, sex, and ethnicity (Japanese). Premorbid intelligence quotient was estimated using the Japanese Adult Reading Test and distress symptoms were assessed using the Hopkins Symptom Check List. Current smoking information was collected according to self-declarations. RESULTS: As expected, the smoking rate was higher, while mean education level and Japanese Adult Reading Test scores were significantly lower, in patients with schizophrenia than in healthy individuals (p < 0.01). The mean education level and Japanese Adult Reading Test scores were significantly lower in the smoker group than in the non-smoker group in both patients and healthy individuals (p < 0.05). In the patient group alone, Hopkins Symptom Check List subscale and total scores were significantly higher in the smoker group than in the non-smoker group (p < 0.05). A multivariate regression analysis showed that the Japanese Adult Reading Test score was a significant and negative predictor for smoking (p < 0.001, odds ratio = 0.97; 95% confidence interval: 0.96–0.99). CONCLUSION: Our results suggest that lower estimated premorbid intelligence quotient is an important variable in elucidating smoking behavior in humans and may be associated with higher prevalence of smoking in patients with schizophrenia.